Temperature Dependent Piezoelectric Properties of Lead-Free (1-x)K0.6Na0.4NbO3–xBiFeO3 Ceramics - Khesro, Amir; Wang, Dawei; Hussain, Fayaz; Muhammad, Raz; Wang, Ge; Feteira, Antonio; Reaney, Ian M. (Frontiers in Materials, 2020)
(1-x)K0.4Na0.6NbO3–xBiFeO3 lead-free piezoelectric ceramics were successfully prepared in a single perovskite phase using the conventional solid-state synthesis. Relative permittivity (εr) as a function of temperature indicated that small additions of BiFeO3 not only broadened and lowered the cubic to tetragonal phase transition (TC) but also shifted the tetragonal to orthorhombic phase transition (TO–T) toward room temperature (RT). Ceramics with x = 1 mol.% showed optimum properties with small and large signal piezoelectric coefficient, d33 = 182 pC/N and d∗33 = 250 pm/V, respectively, electromechanical coupling coefficient, kp = 50%, and TC = 355°C. kp varied by ∼5% from RT to 90°C, while d∗33 showed a variation of ∼15% from RT to 75°C, indicating that piezoelectric properties were stable with temperature in the orthorhombic phase field. However, above the onset of TO–T, the properties monotonically degraded in the tetragonal phase field as TC was approached.